Developing a stress reaction inventory for eye care workers (Ukrainian Journal of Ophthalmology, 2025)
Background: The job-related burnout rate in eye care workers has been consistently rising. That is why it is important to develop psychodiagnostic instruments for detecting stress reactions, and to make them psychometrically adapted to the social and cultural realities of the Ukrainian professional environment.Purpose: To develop an inventory for measuring stress reactions, to customize it to eye care workers and the realities of our nation, to psychometrically analyze it, and to estimate its relationships with job satisfaction indices.Materials and Methods: The study sample consisted of the eye care workers from the Filatov institute. Two hundred and eleven eye care workers were included in the study. The response rate for the inventory was 85.8% (181/211). The 181 responders included 99 nursing staff members and 82 physicians (ophthalmologists). The study was conducted with the use of the modified version of the Student-life Stress Inventory (SSI) by Gadzella.Results: The Stress Reaction Inventory (SRI) for eye care workers was developed by adapting the SSI. The modified version of the inventory is comprised of four stress reaction scales (or categories), Physiological (F), Emotional (G), Behavioral (H), and Cognitive Appraisal (I), which were found to have high internal consistency and test-retest reliability. Both among the nursing staff member group and the physician group, the more acute emotional and behavioral reactions to stressors responders experienced, the lower was their job satisfaction. The test norms were developed and presented using the quartile scale, as long as the sample was representative. Therefore, the adapted Ukrainian-language version of the Stress Reaction Inventory for eye care workers showed evidence of internal consistency and construct validity.
Keywords: stress reactions; job satisfaction; inventory; standardization; ophthalmologists